Degradation of the plasma sprayed GdMgAl11O19 thermal barrier coating resistant to calcium-magnesium-aluminum-silicate attack at 1350 °C. (June 2020) - Sun, Yiwei; Wu, Hengkai; Chen, Xiaolong; Deng, Chunming; Wu, Duoli; Cao, Xueqiang; Li, Wei
Highlights: Plasma sprayed GdMgAl11 O19 (GdMA) is proposed as a new CMAS resistant coating. CMAS degradation mechanism of GdMA coating at 1350 °C is reported for the first time. GdMA coating shows much better CMAS resistance than YSZ coating at 1350 °C. Gd, Mg and Al in GdMA are effective agents for arresting melted CMAS penetration. Abstract: Degradation of plasma sprayed GdMA and YSZ coatings attacked by CMAS was comparatively investigated at 1350 °C for 1 h, 12 h and 48 h in air. Results show that GdMA coating exhibited much better CMAS attack resistance than the YSZ coating. Presences of Gd, Mg and Al elements facilitated formations of the Ca2 Gd8 (SiO4 )6 O2 apatite, MgAl2 O4 spinel and CaAl2 Si2 O8 anorthite crystals effectively arresting the molten CMAS glass penetration. YSZ coating underwent a typical dissolution-precipitation degradation mode. Precipitated fine ZrO2 grains leading to significantly increased grain boundaries provided pathways for further penetration of the melted CMAS causing a more and more serious degradation to YSZ coating along thickness direction as duration extended. GdMA coating with amorphous phase provided enough Al 3+ dissolved in melted CMAS leading to fast formation of CaAl2 Si2 O8 crystals first. Local enrichment of Mg 2+ concentration from the starting CMAS and as well as GdMA dissolution contributed to formations of the MgAl2 O4 crystals. Ca2 Gd8 (SiO4 )6 O2 apatite crystals growth was Gd 3+ concentration and local CMAS loading controlled, they effectively healed the vertical microcracks induced by crystallization of amorphous phase. CaAl2 Si2 O8 anorthite mainly as the top layer, MgAl2 O4 spinel mainly as an relative thin intermediate layer followed by a third layer mainly consisting of Ca2 Gd8 (SiO4 )6 O2 apatite and integrity GdMA phase generally contributed to an entire degradation layer of the CMAS-degraded GdMA coating.